Gasdermin B (GSDMB) in psoriatic patients–a preliminary comprehensive study on human serum, urine and skin - Nowowiejska, Julia; Baran, Anna; Pryczynicz, Anna; Hermanowicz, Justyna Magdalena; Sieklucka, Beata; Pawlak, Dariusz; Flisiak, Iwona (Frontiers in Molecular Biosciences, 2024)
Psoriasis is one of the most common skin diseases and a crucial issue to manage in contemporary dermatology. The search for the details of its pathogenesis, markers and treatment is continuously ongoing. Our aim was to investigate the role of gasdermin B (GSDMB) in psoriasis, the second protein from the gasdermin family, involved in cell death and proliferation. GSDMB serum and urinary concentrations have never been studied in psoriatics, neither tissue expression of GSDMB by immunohistochemistry. The study included 60 psoriatic patients and 30 volunteers without dermatoses as controls. The serum and urinary GSDMB were evaluated by ELISA. Tissue expression of GSDMB was analyzed by immunohistochemistry. The serum and absolute urine concentrations of GSDMB were significantly higher in psoriatic patients than controls without skin diseases (p=0.0137, p=0.039 respectively). Urinary GSDMB/creatinine concentration ratio was significantly lower in patients compared to controls (p=0.0241). The expression of GSDMB in the dermis and epidermis was significantly more prevalent in psoriatic plaque compared to the non-lesional skin and healthy skin of controls (p=0.0012, p=0.017, respectively). Serum GSDMB correlated positively with the age of patients (R=0.41; p=0.001). Our study adds to the current state of knowledge about psoriasis concerning the potential involvement of GSDMB in psoriasis pathogenesis. Most Possibly it could be engaged in keratinocytes migration, which requires further research. Elevated serum GSDMB and decreased urinary GSDMB/creatinine concentration ratio could potentially be investigated as psoriasis biomarkers. GSDMB could be investigated in the future as a potential therapeutic target.